HERMENEUTIKA, SEBUAH CARA UNTUK MEMAHAMI TEKS - Acep Iwan Saidi (Fakultas Seni Rupa dan Desain ITB, 2008)
Hermeneutics is a theory that deals with text interpretation. This theory is commonly used as a method to understand a text although Hermeneutics itself does not explicitly formulate the practical steps to understand a text. Among the theories of interpretation, Hermeneutics has various sub-interpretation theories. In the perspective of Hermeneutics, the initail stage of interpretation involves the objective interpretation of a text before symbolization is made. The message of the text is then related to the other elements of the texts such as the sender of the text, other related disciplines, and socio-cultural aspect of the text. The understanding of a text will eventually be identical with the quality improvement of the interpreter's own self. However, in practice, Hermeneutics can be used to intrepret various texts. This paper will only discusses the text of artistic and literary work. These two different texts will be analyzed by using one of the perspectives of Hermeneutics in a simple and applicable formulation. Key words: interpretation, objective text teks, symbolization, methapora, layers of meaning, one own's self quality